Analysis learning outcomes of mathematics education student in the online learning - Christina Sitepu; Sanggam P. Gultom; Agusmanto J. B. Hutauruk; Simon M. Panjaitan (IKIP Siliwangi and I-MES, 2024)
This research aims to look at the impact and learning outcomes of using LMS and online learning platforms, so it is necessary to analyze learning outcomes and how they impact students, lecturers, and learning organizing institutions. This research shows that the LMS and online learning platforms used can improve student learning outcomes, which cannot be separated from the readiness of lecturers and students to implement it. This research used factor analysis (CFA), with a total of 150 respondents, students, and 15 lecturers. The impact provided by the use of LMS and online platforms in online learning is in the form of GPA and students' views on the learning process they have gone through. From the research results, several findings were obtained, including the ability to use LMS in online learning is not optimal, the GPA of learning outcomes is relatively high, and the readiness of lecturers and students to use LMS in online learning is still low.